Design of Light Control Sub-system Based on Pulse Width Modulation to Perfect The First Generation of UIN Sunan Kalijaga’s High Power UVLED Fluorescence Spectroscopy System - Rakhmadi, Frida Agung; Makhfudloh, Anis Bahirah Ulfa; Rifai, Rochan; Kurniawan, Ade (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Research on design of a light control sub-system based on pulse width modulation (PWM) to perfect the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy sstem has been done. The purpose of this research was to design a light control sub-system based on PWM to perfect the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system. This research was done in two steps, firstly was designing a light control sub-system separated from the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system and secondly was designing a light control sub-system integrated into the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system. Both were designed using CorelDraw software. The result showed that a design of a light control sub-system separated from the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system has been made succesfully using CorelDraw. So as a design of a light control sub-system integrated into the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system.